E-Service Quality, Technology Self-Efficacy and Smart Banking Adoption in Sri Lanka - Nayanajith, Gayan; Damunupola, K. A.; Pastor, Cherish Kay L (ASEAN Multidisciplinary Research Journal, 2020)
Alongside the increasing usage of smart devices across the industries for the delivery of secure and efficient services, technology self-efficacy is an emerging research notion amongst the scholars. Present research analyses the effect of technology self-efficacy (TSE) and e-service quality (ESQ) towards adoption of smart banking (AoSB) in Sri Lankan commercial banking context. Sample was drawn from Kelaniya University students those who are using smart banking services. Data analysis was performed using 287 questionnaires by using hierarchical linear model. TAM has been extended using the TSE and ESQ variables. Empirical evidence supported the significance of ESQ, TSE and interaction effect (TSE and motive towards TSE) aspects on AoSB. Usage of only the quantitative methods and constrained sample were limitations of the study. However, findings are beneficial for banks, banking application and fintech developers, the same. Originality of the research is that the application of the hierarchical linear model and combination of TAM with variables adopted from SCT and SERVQUEL models, given the specific research context. Upcoming researches could be performed in different contexts by incorporating diverse models and perspectives.